Nation Branding Strategy for Zimbabwe: Towards an Integrated Nation Branding Framework - Masango, Cleven; Naidoo, Vannie (Journal of Accounting, Business and Finance Research, 2019)
This article examines the development of nation brand strategy framework for Zimbabwe. The submission is based on the analysis of factors perceived to impact on nation branding programmes. This research aim to contribute towards the development of effective nation branding discourse and practice in Zimbabwe. Specifically, the article was premised on the quest to 1) determine key determinants for the development of Brand Zimbabwe; 2) to ascertain the relative significance of the various facets of national branding practice; and 3) to propose an integrated conceptual framework for nation branding initiatives. The study was designed to follow a mixed approach; a combination of interpretivism and positivism. A total of 372 respondents was drawn from across the society. Respondents came from politicians, scholars, the media, civic organisations, government officials, church and international organisations. This research established that Brand Zimbabwe requires an independent body to integrate all key stakeholders for an effective branding process. The nation branding process should be managed from visioning, formulation through to deployment and monitoring and control of nation brand performance. Zimbabwe’s quest for foreign direct investment, international visitation and export revenue requires that the country develops an integrated strategy to deal with its nation brand image question.